Application of Optical and Electron Microscopy to Coal Conversion Systems - L. A. Harris (The Minerals, Metals and Materials Society, 1982)
The formation of coke during coal liquefaction can eventually result in catastrophic failure of the conversion system. Coking typically proceeds by the formation of liquid crystals (mesophase) and the subsequent separation of these crystals from the plastic phase formed during heating of coal. The anisotropy of the mesophase makes it readily detectable in the optical microscope under polarized light. This study examines the solids formed during coal liquefaction processing by optical and electron microscopy. Observations on the relationships between the coke morphology, minerals and inert macerals are presented.